Pentecostal Conceptions of Evil Forces: An Exposition on Warfare Prayer and Imprecation in Modern Nigeria - Jemimah Ogechi Ekechi (E-Journal of Religious and Theological Studies)
This study critically examines the deceptive nature of magic and witchcraft as cultural practices in Zimbabwe and highlights its negative impact on society. Based on social conflict theory, the research explores how the belief in witchcraft fosters fear, suspicion, and social division, perpetuating conflict within families and communities. Witchcraft, often considered a form of cultural heritage, is scrutinised not only for its historical significance but also for the ways in which it undermines social cohesion and development. The study employed a qualitative methodological approach, using a combination of ethnographic accounts and a literature review to gather insights from local communities, traditional leaders, and scholars. By analysing narratives from individuals who have been affected by witchcraft accusations or practices, the research revealed the deep-seated anxieties and tensions that witchcraft engenders. This paper argues that although cultural traditions should be valued, harmful practices such as witchcraft must be discouraged to foster social harmony and progress in Zimbabwe. The discussion calls for a collective effort to address this menace and to reimagine cultural practices in a way that promotes unity, peace, and development. This study contributes to scholarship by offering a critical cultural analysis that challenges the romanticisation of witchcraft as heritage, presenting a framework for evaluating cultural practices through their social consequences. It adds to the discourse on cultural reform and social justice, particularly in postcolonial African societies seeking pathways to development grounded in ethical and inclusive traditions.